Addition of urea to finishing cattle diets containing steam-flaked corn and wet corn gluten feed - Sean P. Montgomery; J.J. Sindt; T.B. Farran; N.J. Pike; C.M. Coetzer; H.J. LaBrune; A.M. Trater; R.D. Hunter; R.A. Stock; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2001)
Three hundred thirty-nine crossbred beef heifers were used in a 74-day finishing study to evaluate effects of adding 0.5% urea to finishing diets containing steam-flaked corn and 34% (dry basis) Sweet Bran® wet corn gluten feed (WCGF). Diets were fed once daily ad libitum. Urea addition tended (P<0.06) to increase finishing average daily gain, to improve (P<0.12) feed efficiency, and to increase (P<0.06) fat thickness. Heifers fed urea had a lower percentage (P<0.03) of carcasses grading USDA Choice. This study suggests that finishing diets containing a combination of steam-flaked corn and WCGF may benefit from addition of urea as a source of supplemental ruminally available nitrogen.
Keywords: Cattlemen' s Day; 2001; Kansas Agricultural Experiment Station contribution; no. 01-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 873; Beef; Wet corn gluten feed; Urea; Finishing